The method of forming a dynamic projects portfolio of IT companies - Moskalenko, Valentina; Fonta, Nataliia; Grinchenko, Marina (CEUR Workshop Proceedings, 2020)
The formation of the IT company project portfolio considered within the confines of strategic development planning. It is proposed that the formation of the portfolio be carried out based on the criterion of maximizing the utility function. The utility function is formed as an additive convolution of the utility functions of the efficiency criteria, risk and benefit from the implementation of this project for the company’s development. It is suggested to consider the totality of IT company project portfolios by years of the planned strategic period as a dynamic object. The process of forming a dynamic project portfolio has two stages: at the first stage, the strategic task of forming a dynamic portfolio is solved as a set of portfolios by years of the planning period; at the second stage, this portfolio is managed. Management involves changing the composition of the portfolio according to the changing policies by the years of the planning period. Company policies during the planning period are adjusted depending on changes in the situation in the IT market. Some results of the implementation of the dynamic portfolio formation method for Ukrainian IT-company are presented. The implementation of this method allowed the project office to rationally plan the company resources, determine activity directions in the IT market, and adjust the development policy of the company on the strategic period.
Keywords: dynamic project portfolio; company development; company policy; utility function